Membaca Ulang Konsep Jihad dalam Al-Qur’an: Usaha Merevitalisasi Islam Rahmat - Darmawan Darmawan (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This paper discusses about re-reading the concept of jihad in the Quran, and focuses on investigating its ethical and practical aspects, followed by the explanation of hadith and books of tafseer dhahiri and bathini. It is starting from several reasons; one of which is the emergence of radicalism that carries the doctrine of jihad. To know the meaning of jihad and variety of jihad and its purposed object in the Quran, the verses meaning and correlating with the study of jihad will be united and analyzed by using thematic (maudhui) theory. Having concluded, Jihad in the Quran is struggling unstoppably by sacrificing all of things that a servant has until reaching the struggled goals: struggling by soul, wealth, or everything that a servant has, with the intention to get the acceptance (ridha) of God (Allah). Having founded, the verses’ talking about jihad do not clearly mention their objects. There are only two objects that are mentioned clearly: battling the unbelievers and hypocrites, but It does not mean, the only two objects that must be faced. By concerning other verses’ that do not mention their objects are much more than the verses’ that mention their objects, This means that Jihad must be not interpreted for only battling the unbelievers and hypocrites. However, it signs that jihad can be applied to all of the human’s activities keeping founded on Islamic doctrines which are dominated by mercies.